Super-shrinkable tape for water-induced automatic wound closure

By using a super-shrinkable film crosslinked with α-cyclodextrin and oriented polyethylene oxide, combined with cyanoacrylate adhesive, the problems of instability and insufficient shrinkage force of existing wound closure materials under environmental conditions are solved, achieving rapid and convenient wound closure, suitable for wounds with bleeding or high tension.

CN120826429APending Publication Date: 2025-10-21NANYANG TECH UNIV

Patent Information

Application Number
CN202480017283.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-07
Filing Date
2024-03-07
Publication Date
2025-10-21

AI Technical Summary

Technical Problem

Existing wound closure materials are unstable under environmental conditions, have insufficient contractility, require additional equipment stimulation, are not suitable for wounds with bleeding or high tension, and lack convenience and self-care ability.

Method used

A super-shrinkable film composed of cross-linked α-cyclodextrin and oriented polyethylene oxide crystal domains is used to induce rapid and significant shrinkage through water wetting, providing high Young's modulus and ultra-large shrinkage stress. Combined with cyanoacrylate adhesive, it is made into a super-shrinkable wound dressing.

Benefits of technology

It is stable under environmental conditions and shrinks rapidly and significantly after being wetted with water, providing ultra-high shrinkage stress and output power density. It is suitable for wounds with bleeding or high tension, simplifies the wound closure process, and improves the convenience of self-care.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120826429A_ABST
    Figure CN120826429A_ABST
Patent Text Reader

Abstract

The present invention relates to super-contractible films, super-contractible wound dressings comprising the super-contractible films, methods of forming the super-contractible films, methods of treating wounds comprising steps of applying the super-contractible wound dressings, and uses of the super-contractible wound dressings. The super-shrinkable film comprises an alpha-cyclodextrin crystal domain; and oriented polyethylene oxide crystalline domains physically crosslinked by alpha-cyclodextrin crystalline domains wherein the polyethylene oxide has a number average molecular weight of from 200,000 to 10,000,000 Daltons; and after the super-shrinkable film is wetted by water, the shrinkage of the super-shrinkable film exceeds 50% of the original length of the super-shrinkable film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a super-shrinkable film, a super-shrinkable wound dressing comprising the super-shrinkable film, a method for forming the super-shrinkable film, a method for treating a wound comprising the step of applying the super-shrinkable wound dressing, and uses of the super-shrinkable wound dressing. Background Art

[0002] The listing or discussion of a previously published document in this specification should not necessarily be taken as an admission that the document is part of the state of the art or is common general knowledge.

[0003] Due to the high incidence of skin wounds, wound healing remains one of the most important issues in healthcare. A key process in wound healing is wound closure, which helps stop bleeding, reduce the risk of infection, speed up healing, protect underlying tissues, and minimize scarring (Oper. Tech. Sports Med. 2011, 19, 206; Chem. Soc. Rev. 2015, 44, 1820; Chem. Rev. 2021, 121, 11336). Traditional wound closure methods such as sutures and tissue adhesives are not convenient for self-care treatment, especially for bleeding wounds. In addition, traditional sutures for wound closure are time-consuming, require professional skills, and cause additional pain and tissue damage.

[0004] Sutures are a common treatment for wound closure. Although they have been used for decades, they still have some limitations, such as being time-consuming, causing additional pain, and requiring trained personnel and specialized tools to perform. Furthermore, to access tissue edges, sutures with a certain amount of stress penetrate surrounding healthy tissue, adding additional pain, increasing the risk of infection, and producing larger scars.

[0005] In recent years, tissue adhesives have become an alternative to sutures, especially for lacerations (Tissue adhesives for traumatic lacerations in children and adults (Review) from Cochrane Database Syst. Rev. 2002; Prog. Polym. Sci. 2014, 39, 1375; Mater. Sci. Eng., C 2020, 111, 110796). Compared with sutures, they do not require professional skills and can relieve the patient's pain without causing additional tissue damage. However, in terms of skin wound closure, tissue adhesives cannot be applied to bleeding wounds and wounds with greater tension (Arch. Dermatol. 2001, 137, 1177; J. Plast. Reconstr. Aesthet. Surg. 2022, 75, 183). The wound edges must be precisely aligned until the adhesive cures to avoid spreading into the wound, which would hinder wound healing and result in poor cosmetic results (Am. Fam. Physician 2000, 61, 1383; J. Maxillofac. Surg. 2010, 1, 15). In addition, the wound edges should be kept close and in close contact with each other before and after the application of the tissue adhesive until it cures, which means that the injured person needs the help of others, which is inconvenient, especially during emergency treatment and unassisted self-care / treatment ( Figure 1 ). Therefore, tissue adhesives are currently used only as a supplement to wound closure sutures.

[0006] Developing an automated wound closure process could help patients manage their wounds immediately, especially in emergency care. In recent years, stimulus-responsive shrinkable materials have shown potential applications in automated wound closure (Science. 2002, 296(5573), 1673-1676; Science Advances. 2019, 5(7), eaaw3963; Materials & Design. 2020, 194, 108916). Due to differences in wound size and skin tension, the force required to close human skin wounds varies greatly. For example, lacerations and elliptical excisions with reported wound gaps of approximately 5-20 mm and wound lengths of 10-50 mm require forces in the range of 0.1 N to 3 N (Med. Biol. Eng. Comput. 1994, 32(6), 638-642; Med Biol Eng Comput. 2012, 50(2), 193-198; Sci. Rep. 2016, 6(1), 301-17; IEEE Journal of Translational Engineering in Health and Medicine. 2022, 10, 1-9). Therefore, a shrinkable material for wound closure should generate sufficient force and energy to close the wound regardless of skin tension differences. In addition, for emergency and self-care applications, it needs to shrink quickly and stabilize before use. Body temperature-triggered shrinkable hydrogels have been developed as active dressings to accelerate wound closure (Science Advances. 2019, 5(7), eaaw3963; Mater. Des. 2020, 194, 108916; Matter 2021, 4, 2985; Adv. Mater. 2021, 33, 2106175). However, these membranes exhibit slow shrinkage or instability under ambient conditions. In addition, their relatively low Young's modulus, contractile force, and contractile work density make them unsuitable for areas with high skin tension (Med. Biol. Eng. Comput. 1994, 32, 638; Med. Biol. Eng. Comput. 2012, 50, 193; Sci. Rep. 2016, 6, 30117; IEEE J. Transl. Eng. Health Med. 2022, 10, 1).Based on the pre-stretching energy storage process, thermoresponsive materials with high work density and higher Young's modulus (Journal of the American Chemical Society.2019,141(36),14364-14369), photoresponsive materials (Adv.Funct.Mater.2020,30(32),2002451) and acid-responsive materials (Science Advances.2020,6(47),eabd2520) have been developed. However, high temperature, acidity and short wavelength light (ultraviolet (UV) light) are not good for the skin. Materials with large contractile forces induced by high temperature (Journal of the American Chemical Society. 2019, 141(36), 14364-14369), light (Adv. Funct. Mater. 2020, 30(32), 2002451) and chemicals (Science Advances. 2020, 6(47), eabd2520) are not skin-friendly or require additional equipment. In addition, additional equipment is required to generate stimulation, such as high temperature and light, which is inconvenient, especially for emergency treatment. It remains a challenge to prepare contractile materials that are compatible with the precious human body, stable under ambient conditions, exhibit large and rapid contraction, generate ultra-large contractile forces, and have ultra-large wound closure application work.

[0007] Automatic skin wound closure requires that the shrinkable film remains stable under ambient conditions to prevent premature contraction, while showing rapid and significant contraction under benign and direct stimulation during use. Recently reported naturally triggered (25°C water) shape memory hydrogels show controllable initiation characteristics, which prevent premature shape changes before use by internal mass diffusion (Nature 2023,622,748). However, these hydrogels exhibit small contraction strain. Another reported block copolymer artificial muscle of PS-PEO-PS (PS: polystyrene; PEO: poly(ethylene oxide)) has excellent water-responsive contraction performance (contraction stress: ~5.5MPa) (Nat.Nanotechnol.2022,17,752). However, they are in a one-dimensional fiber state with a diameter in the micron range.

[0008] Water-responsive shape-adaptive membranes based on oriented PEO domains have been previously developed (WO2023 / 075689A2). The highly stretched PEO domains cross-linked by poly(ethylene glycol)-α-cyclodextrin (PEG-α-CD) inclusion complex (IC) make the membrane stable under ambient conditions, but shrink rapidly and significantly when wetted. However, this porous membrane exhibits a low post-shrinkage Young's modulus (~100 kPa) and a relatively low shrinkage force (shrinkage stress: ~2 MPa) ( Figure 2 The porous structure also results in high opacity, hindering the user's ability to observe the wound beneath the membrane ( Figure 3 ). Therefore, these obstacles need to be overcome. Summary of the Invention

[0009] Surprisingly, it was found that super-shrinkable films (SC films) constructed from poly(ethylene oxide) (PEO) and α-cyclodextrin (α-CD) have high Young's modulus (dry state: ∼600 MPa, re-dried state: ∼130 MPa) and show large (∼50%) and rapid (12% / s) water-responsive shrinkage. α-CD was used instead of PEG-α-CD inclusion complex (IC) to directly crosslink PEO to form non-porous, dense, water-responsive super-shrinkable films (SC films for wound closure). Figure 4 ab). These α-CD / PEO SC films are translucent and flexible ( Figure 4 c), stable at ambient temperature and humidity, shrinks significantly (~50%) within seconds when wetted, and produces ultra-large shrinkage stress (~6MPa) and output power density (~1028kJ / m 3 Such contractile stress and output power density greatly exceed those of skeletal muscle (IJOE.2004,29(3),706-728) (~0.35MPa,~40kJ / m 3 )、Shrinkable LCE (Adv.Funct.Mater.2020,30(32),2002451;Macromolecules.2021,54(12),5397-5409)(~0.2MPa,~80kJ / m 3 ) and hydrogels (Science Advances, 2020, 6(47), eabd2520)(~2-40kPa,~0.01-15kJ / m 3 Furthermore, the SC membrane is stable under ambient conditions and can lift objects 10,000 times its own weight when wet. The super-shrinkable film can be applied to water-shrink tapes, which can be used to compress healthy human skin from various locations to produce displacements greater than 30%. As disclosed herein, water-shrink tapes according to the present invention promoted wound healing and accelerated hemostasis in rat and rabbit wound models.

[0010] Various aspects and embodiments of the invention will now be described with reference to the following numbered clauses.

[0011] 1. A super-shrinkable film comprising:

[0012] α-cyclodextrin crystalline domains; and

[0013] Oriented polyethylene oxide crystalline domains physically cross-linked by said α-cyclodextrin crystalline domains, wherein:

[0014] The polyethylene oxide has a number average molecular weight of 200,000 to 10,000,000 Daltons; and

[0015] The supershrinkable film shrinks more than 50% of its original length upon wetting with water.

[0016] 2. The super-shrinkable film according to clause 1, wherein the oriented polyethylene oxide crystalline domains exhibit anisotropy in a dry state before contact with water.

[0017] 3. The super-shrinkable film according to clause 1 or clause 2, wherein the super-shrinkable film exhibits a shrinkage rate of 10 to 50% / s relative to its original length after being wetted with water.

[0018] 4. The super-shrinkable film of clause 3, wherein the super-shrinkable film exhibits a shrinkage rate of about 12% / s relative to its original length after being wetted with water.

[0019] 5. An ultra-shrinkable film according to any of the preceding clauses, wherein the weight:weight ratio of polyethylene oxide:α-cyclodextrin is 3:1 to 1:10, such as 1:1.5 to 1:9, such as 1:1.6 to 1:3.33, such as 2:5 to 3:5, such as about 2:5, or such as about 3:5.

[0020] 6. A super-shrinkable film according to any of the preceding clauses, wherein one or more of the following apply:

[0021] (a) the super shrinkable film is stable at a temperature below 60° C. and a relative humidity below 70%;

[0022] (b) the polyethylene oxide has a number average molecular weight of 500,000 to 7,000,000 Daltons, such as 750,000 to 5,000,000 Daltons, such as 1,000,000 to 3,000,000 Daltons, such as about 2,000,000 Daltons; and

[0023] (c) The ultra-shrinkable film does not include a crystalline inclusion complex domain formed by poly(pseudo)rotaxane or polyrotaxane formed by α-cyclodextrin and polyethylene glycol having a number average molecular weight of 500 to 10,000 Daltons.

[0024] 7. A super-shrinkable film according to any of the preceding clauses, wherein the super-shrinkable film has a Young's modulus of 50 MPa to 1 GPa, such as 200 to 850 MPa, such as 400 to 700 MPa, such as about 600 MPa, optionally wherein the super-shrinkable film has a Young's modulus of 100 kPa to 2 MPa, such as 200 kPa to 1 MPa after being wetted with water, and after the wet super-shrinkable film is dried, the Young's modulus is several hundred MPa, such as 100 MPa to 700 MPa.

[0025] 8. A supershrinkable film according to any of the preceding clauses, wherein the supershrinkable film has been longitudinally stretched to provide oriented polyethylene oxide domains, wherein the longitudinal stretching results in a film having a length of 200 to 1,000%, such as 250 to 700%, such as 300 to 500%, such as about 400%, of the original length of a freestanding film material comprising:

[0026] α-cyclodextrin crystalline domains; and

[0027] Unoriented polyethylene oxide domains physically cross-linked with crystalline inclusion complex domains.

[0028] 9. A super-shrinkable film according to any of the preceding clauses, wherein one or more of the following apply:

[0029] (i) the super-shrinkable film shrinks by 35 to 65% of its original length upon wetting with water;

[0030] (ii) the maximum shrinkage stress of the super shrinkable film is 2.5 to 7 MPa, such as 2.7 to 6.5 MPa, such as 3 to 6 MPa; and

[0031] (iii) the super-shrinkable film releases an energy density of 450 to 1,800 kJ / m upon contact with water 3 , such as 480 to 1,730 kJ / m 3 , such as 600 to 1,300 kJ / m 3 , such as 630 to 1,240 kJ / m 3 .

[0032] 10. A super-contractible wound dressing comprising:

[0033] a first layer of a supershrinkable film according to any one of clauses 1 to 9 having a first surface and a second surface; and

[0034] A second layer of adhesive material applied to the first surface of the first layer, wherein the adhesive material does not cause supershrinkage of the supershrinkable film.

[0035] 11. The ultra-shrinkable wound dressing of clause 10, wherein a drop of the adhesive material has a contact angle on the ultra-shrinkable film surface of 0° to 30°, such as 5° to 25°, such as 10° to 20°.

[0036] 12. A super-contractible wound dressing according to clause 10 or clause 11, wherein the adhesive material is a cyanoacrylate adhesive, such as a cyanoacrylate tissue adhesive.

[0037] 13. The super-contractible wound dressing according to clause 12, wherein the adhesive material is selected from one or both of N-butyl-2-cyanoacrylate and 2-octyl-cyanoacrylate.

[0038] 14. A method of forming a super-shrinkable film according to any one of clauses 1 to 9, the method comprising the steps of:

[0039] (ai) Providing a freestanding film comprising:

[0040] α-cyclodextrin crystalline domains; and

[0041] Non-oriented polyethylene oxide domains physically cross-linked to crystalline inclusion complex domains, wherein:

[0042] The polyethylene oxide has a number average molecular weight of 200,000 to 10,000,000 Daltons; and

[0043] (aii) stretching a film by applying strain so that the elongation of the film reaches 100% to 300% of its original length to provide a super-shrinkable film.

[0044] 15. The method of clause 14, wherein the method further comprises further repeatedly stretching the super-shrinkable film by applying strain to obtain a desired length, optionally wherein the desired length is 200 to 1,000%, such as 250 to 700%, such as 300 to 500%, such as about 400%, of the original length of the free-standing film.

[0045] 16. A method according to clause 14 or clause 15, wherein the strain is 10 to 100 MPa, such as 25 to 75 MPa, such as about 50 MPa.

[0046] 17. A method according to any of clauses 14 to 16, wherein the stretching involves a stretching speed of 0.1 to 5 mm / s, such as about 2 mm / s.

[0047] 18. A method according to any one of clauses 14 to 17, wherein the polyethylene oxide has a number average molecular weight of 500,000 to 7,000,000 Daltons, such as 750,000 to 5,000,000 Daltons, such as 1,000,000 to 3,000,000 Daltons, such as about 2,000,000 Daltons.

[0048] 19. The method according to any one of clauses 14 to 18, wherein the super-shrinkable film does not comprise a crystalline inclusion complex domain formed by a poly(pseudo)rotaxane or a polyrotaxane formed by α-cyclodextrin and polyethylene glycol having a number average molecular weight of 500 to 10,000 Daltons.

[0049] 20. A method of forming a freestanding membrane as described in Clause 14, the method comprising:

[0050] (bi) providing a composition comprising α-cyclodextrin and a solvent;

[0051] (bii) adding poly(ethylene oxide) (PEO) to the composition and aging it for a period of time at a temperature of 40 to 80° C., such as about 60° C., to provide a freestanding membrane precursor solution; and

[0052] (biii) drying the freestanding membrane precursor solution to provide a freestanding membrane precursor.

[0053] 21. A method of treating a wound, the method comprising the step of applying a super-contractible wound dressing according to any one of clauses 10 to 13 for a period of time to assist wound healing.

[0054] 22. Use of a super-contractible wound dressing according to any one of clauses 10 to 13 for wound healing.

[0055] 23. Use of a super-contractible wound dressing according to any one of clauses 10 to 13 in the manufacture of a medicament for treating a wound. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 Schematic diagrams depicting a comparison of sutures, tissue adhesives, and water-shrink tapes for skin wound closure. (a) Schematic diagram of traditional wound closure procedures using sutures and tissue adhesives. Suturing requires trained personnel and specialized tools. Tissue adhesives cannot be applied to bleeding wounds or wounds with high tension, and the wound must be closed before the adhesive cures. (b) Schematic diagram of a water-shrink tape constructed from SC membrane for water-induced automatic skin wound closure. The water-shrink tape is easy to implement and can be applied to bleeding wounds without additional stimulation.

[0057] Figure 2The maximum shrinkage stress of water-responsive shape-adaptive polymer (WRAP) films (WO 2023 / 075689 A2) with different elongations when sprayed with water is depicted. The shrinkage stress ranges from 1.5 to 2.3 MPa.

[0058] Figure 3 Depicted is a WRAP membrane composed of a PEO and PEG-α-CD inclusion complex. (a) The WRAP membrane is white and opaque. (b) An excised porcine skin wound beneath the WRAP membrane. The high opacity of the WRAP membrane makes it difficult to visualize the wound beneath. Scale bar: 5 mm.

[0059] Figure 4 Depicted is the design of a water-responsive, super-shrinkable film (SC film) for automated wound closure. (a) Schematic diagram of a water-shrinkable tape constructed from SC film for water-induced automated skin wound closure. The water-shrinkable tape is easy to implement and can be applied to bleeding wounds without additional stimulation. (b) The SC film is composed of α-CD and high molecular weight (2,000,000) PEO. (c) The SC film is translucent and flexible, allowing for easy folding. Scale bar: 5 mm.

[0060] Figure 5 Depicted is the fabrication of super-shrinkable films for super-shrinkable tapes. (a) α-CD / PEO (5:3 mass ratio) mixture before defoaming and solvent casting. (b) Freestanding α-CD / PEO film after drying.

[0061] Figure 6 Depicted is an SC membrane prepared by repeated cold stretching of a post-yield α-CD / PEO membrane. In each cycle, the yielded 5:3 α-CD / PEO membrane was stretched to a preset stress of 50 MPa and unloaded, returning to its initial position at a speed of 2 mm / s. Inset: α-CD / PEO membrane before (left) and during (right) repeated cold stretching. Scale bar: 1 cm.

[0062] Figure 7 Depicted is the preparation of SC membranes by repeated cold stretching. (a) First, a 5:3 α-CD / PEO membrane was cold stretched to 400% strain and then unloaded at a rate of 2 mm / s to obtain a post-yield membrane without any breakage. (b) A 10:3 α-CD / PEO membrane was cold stretched to 300% strain and then unloaded at a rate of 2 mm / s to obtain a post-yield membrane. The 10:3 membrane easily breaks when directly stretched beyond 300%. (c) In each cycle, we further repeatedly cold-stretched the post-yield 10:3 α-CD / PEO membrane to a preset stress of 40 MPa and unloaded at a rate of 2 mm / s to obtain a 10:3 SC membrane.

[0063] Figure 8The underwater stability of α-CD / PEO membranes with different α-CD to PEO mass ratios is depicted. Stability is greatly improved when the mass ratio is between 5:3 and 10:3.

[0064] Figure 9 The stress-strain curves were plotted, showing that the greater the α-CD content, the higher the Young's modulus.

[0065] Figure 10 The stress-strain curves were plotted, showing that the greater the α-CD content, the higher the Young's modulus and the lower the fracture strain of the α-CD / PEO film.

[0066] FIG11 depicts (a) SC films with different elongation ratios (5:3); and (b) a semi-transparent flexible SC film.

[0067] Figure 12 Depicted are tear tests showing that the SC film (5:3, 500%) has anisotropic mechanical properties. It tears easily along the cold stretching direction (longitudinal direction) and is difficult to tear along the transverse direction. Inset: Photographs of SC films torn transversely (left) and along the cold stretching direction (right), with the former causing film deformation. Scale bar: f, 5 mm.

[0068] Figure 13 Depicted are (a) field emission scanning electron microscopy (FESEM) images of the surface of an α-CD / PEO film (5:3); (b) a FESEM image of the surface of an α-CD / PEO SC film (5:3, 500%); and (c) a longitudinal cross-sectional FESEM image of the SC film (5:3, 500%), showing its oriented structure. Scale bars: a, b, 1 μm; c, 10 μm.

[0069] Figure 14 Depicted are (a) the two-dimensional wide-angle X-ray scattering (2D-WAXS) pattern of an α-CD / PEO film (mass ratio, 10:3). The pattern attributable to PEO crystallites is weak. (b) The 2D-WAXS pattern of an α-CD / PEO film (mass ratio, 5:3). The isotropic 2D-WAXS pattern shows that the structure of the α-CD / PEO film before cold stretching is isotropic. (c) The 2D-WAXS pattern of an SC film (5:3, 500%). The pattern attributable to the PEO crystallite domains is anisotropic, while the pattern attributable to α-CD is isotropic. (d) The 2D-WAXS pattern of the SC film after drying and shrinkage regains isotropy.

[0070] Figure 15Depicted are water-induced supercontractile properties. (a) The SC film exhibits rapid water-induced contraction. The SC film (5:3, 500%) contracts by ~60% in 5 seconds. Scale bar: 5 mm. (b) The contractile strain of the SC film increases with increasing elongation. (c) The post-contracted Young's modulus of the SC film decreases with increasing elongation.

[0071] Figure 16 Figure 3 shows the restrained shrinkage stress of an SC film (5:3, 500%) when sprayed with water. Contraction occurs almost immediately upon spraying with water, reaches a maximum within 1 second, and then partially relaxes.

[0072] Figure 17 Depicted is the measurement of the maximum shrinkage stress by spraying water on a constrained SC film with its gauge length fixed to its original size.

[0073] Figure 18 The stress-strain curves and Young's modulus of dry, wet and redispersed SC films (5:3, 500%) are depicted. The SC film softens when wet and regains rigidity after redispersing.

[0074] Figure 19 The released energy density (W) calculated using the contraction stress-displacement curve is plotted. E ).

[0075] Figure 20 The released energy density of the SC films is depicted. Stress-displacement curves of (a) SC film (5:3, 500%), (b) SC film (10:3, 500%), (c) SC film (5:3, 400%), and (d) SC film (10:3, 400%) are used to calculate the released energy density.

[0076] Figure 21 Depicted are lifting experiments used to calculate the output power density of an SC membrane (5:3, 500%). (a) Photograph of an SC membrane (5:3, 500%) (dimensions: 30 mm × 3 mm × ~40 μm, weight: ~mg) lifting a 10g load in 20 seconds when wetted with water. After drying, the load can be slightly further lifted. (bc) Photographs of an SC membrane (5:3, 500%) (dimensions: 30 mm × 3 mm × ~40 μm, weight: ~4 mg) lifting loads (b) 2-20g and (c) 30g (b) in 20 seconds when wetted with water. Scale bar: 1 cm.

[0077] Figure 22Depicted are: (a) a photograph of an SC membrane (5:3, 500%) lifting an object 10,000 times heavier than itself; and (b) a photograph of an SC membrane (5:3, 500%) (dimensions: 30 mm × 3 mm × ~40 μm, weight: ~4 mg) lifting a 40 g load in 20 seconds when wetted with water. Scale bar: 1 cm.

[0078] Figure 23 The output work density measured by the lifting experiment is plotted. The work done by the SC membrane is calculated upon completion of the rapid contraction after wetting (within 1 min).

[0079] Figure 24 The maximum output work density and contraction strain of various biological and synthetic contractile materials are plotted. Circles represent contractions triggered by water, triangles represent contractions triggered by heat, inverted triangles represent contractions triggered by light, and squares represent contractions triggered by chemicals.

[0080] Figure 25 Shrinkage performance at different relative humidities is depicted. Humidity response testing shows that the SC film hardly shrinks when exposed to RH < 70% for 48 hours. The SC film partially shrinks at RH 75% and 84%, and shrinks significantly at RH 94% and 97% for 48 hours. Even at high RH of 94% and 97%, all samples show negligible shrinkage within 5 minutes. All samples were tested after incubation for different incubation times at room temperature (25°C) at a fixed RH in a sealed chamber.

[0081] Figure 26 Depicting the in vitro biocompatibility of SC membranes. Viability / cytotoxicity assays showed that after 24 hours of culture in conditioned medium prepared by soaking SC membranes (5:3, 500%) in original culture medium, the majority of normal human dermal fibroblasts remained viable, comparable to cells cultured in original culture medium (control). Scale bar: 100 μm.

[0082] Figure 27 Depicted is a schematic diagram of the SC tape for skin wound closure consisting of SC membrane and tissue adhesive.

[0083] Figure 28 Depicted are a supershrinkable tape and its performance on ex vivo porcine and healthy human skin, where contact angle measurements (a) and (b) show good wettability of N-butyl-2-cyanoacrylate on the SC membrane. The cyanoacrylate spreads rapidly on the SC membrane.

[0084] Figure 29Depicted are (a) Adhesion energy measured on ex vivo porcine skin using a 180-degree peel test. The adhesion energy of two conventional cyanoacrylate tissue adhesives showed a slight increase when combined with SC film. (bc) Adhesion properties of SC tape (b) Schematic diagram of the setup for measuring the adhesion energy of SC tape composed of SC film and cyanoacrylate tissue adhesive. (c) Schematic diagram and photograph of a shear test of SC tape (redried) adhered to ex vivo porcine skin. This shows that stretching the redried SC tape adhered to porcine skin did not cause interfacial shear, but rather caused the SC film to stretch. Scale bar: 1 cm.

[0085] Figure 30 Depicts the adhesion of re-dried SC tape (SC membrane / Cyano) to excised porcine skin, demonstrating higher shear strength compared to a commercial soft (Tegaderm™) medical tape and greater extensibility compared to a commercial hard (cotton) medical tape. Cyano refers to N-butyl-2-cyanoacrylate tissue adhesive.

[0086] Figure 31 Depicted is the automated wound closure performance of SC tape on ex vivo porcine skin. Scale bar: 1 cm.

[0087] Figure 32 Schematic representation of the body areas where SC tape was applied (shoulder, forearm, and knee).

[0088] Figure 33 Depicted are (a)-(c) SC tape applied to the skin of a healthy individual's forearm, shoulder, and knee. When wet, the SC tape contracts within 1 minute, significantly compressing the skin. After 30 minutes, the SC tape is dried, further compressing the skin. (d) Skin contraction rate induced by SC tape after 1 and 30 minutes of contraction. Scale bars: d, 1 cm; e, 5 mm.

[0089] Figure 34 depicts in vivo wound closure performance. (a) Representative photographs of wound closure (rat skin) on days 0, 3, and 7 that were untreated or treated with SC tape or sutures. SC tape immediately closed the wound when moistened and promoted wound healing. Scale bar: 5 mm. (b) Histological sections of wound tissue harvested on day 7 stained with hematoxylin and eosin (H&E) and Masson's trichrome. Compared to wounds treated with sutures and untreated wounds, wounds treated with SC tape had smaller areas and denser collagen. Scale bar: 200 μm. (c) Histological sections of wound tissue harvested on day 3 stained with Masson's trichrome. Scale bar: 400 μm. (d) CD68 immunohistochemical staining in wound tissue harvested on day 3. Scale bar: 400 μm. (e) Percentage of collagen fibers calculated from Masson's trichrome staining images of wound tissue harvested on day 3. (f) Positive areas of CD68 immunostaining in wound tissue harvested on day 3. *p<0.05, statistical analysis was performed using one-way ANOVA, followed by Tukey's post hoc test to assess mean differences (n=6). (g) SC tape automatically closed bleeding rabbit skin wounds and stopped bleeding within 1 minute. Linear cuts were applied to shaved rabbit skin to form wounds (length ~2 cm), and the wounds became oval due to the effect of skin tension. Scale: 5 mm. (h) Commercial closure strips were unable to adequately close bleeding wounds. Scale: 5 mm. (i) Wounds treated with hydrocontractile tape bled less than untreated and closure strip-treated wounds. ***p<0.001, ****p<0.0001, statistical analysis was performed using one-way ANOVA, followed by Tukey's post hoc test to assess mean differences.

[0090] Figure 35 Depicted are H&E-stained histological sections of wound tissue harvested on day 3. Blue arrows indicate infiltration of inflammatory cells (neutrophils, lymphocytes, and macrophages). Yellow arrows indicate mild hemorrhage. Brown arrows indicate regenerating hair follicles. Scale bars: Left, 400 μm; Right, 100 μm.

[0091] Figure 36 The humidity stability of supershrinkable films is characterized. DETAILED DESCRIPTION

[0092] Surprisingly, it was found that super-shrinkable films (SC films) constructed from poly(ethylene oxide) (PEO) and α-cyclodextrin (α-CD) have high Young's modulus (dry state: ∼600 MPa, re-dried state: ∼130 MPa) and show large (∼50%) and rapid (12% / s) shrinkage upon exposure to water, as well as ultra-large shrinkage stress (∼6 MPa) and output work density (∼1028 kJ / m 3Such contractile stress and output power density are much higher than those of skeletal muscle (~0.35MPa, ~40kJ / m 3 ), shrinkable LCE (~0.2MPa, ~80kJ / m 3 ) and hydrogels (~2-40 kPa, ~0.01-15 kJ / m 3 ). In addition, the SC membranes disclosed herein are stable under ambient conditions and can lift objects 10,000 times heavier than their own weight when wet. The preparation procedure is simple and suitable for large-scale production. The water stimulation and biocompatible components make them suitable for biomedical applications. In addition, in combination with adhesives suitable for living tissue, super-shrinkable tapes (SC tapes) can be prepared, which have enhanced adhesive strength and can automatically close skin wounds in seconds ( Figure 4 a). Conveniently, the process of applying SC tape to the wound is simple and can be done with just one hand. Therefore, SC tape provides a useful wound closure strategy that overcomes the shortcomings of traditional methods. For example, the application process avoids the problems associated with applying sutures, which are inconvenient to obtain (because suitable medical personnel need to be found), time-consuming to apply, and cause additional pain during (and possibly after) the suturing process. In addition, SC tape is a 2D planar film that can cover the entire wound, which can be integrated with sensors and / or one or more drugs can be loaded into polymeric materials to achieve its use in smart wound monitoring and drug delivery.

[0093] Thus, in a first aspect of the present invention, there is provided a super-shrinkable film comprising:

[0094] α-cyclodextrin crystalline domains; and

[0095] Oriented polyethylene oxide crystalline domains physically cross-linked by said α-cyclodextrin crystalline domains, wherein:

[0096] The polyethylene oxide has a number average molecular weight of 200,000 to 10,000,000 Daltons; and

[0097] The supershrinkable film shrinks more than 50% of its original length upon wetting with water.

[0098] As used herein, the word "comprising" may be interpreted as requiring the features mentioned, but not limiting the presence of other features. Alternatively, the word "comprising" may also refer to situations where it is intended that only the listed components / features are present (e.g., the word "comprising" may be replaced by the phrase "consisting of" or "consisting essentially of"). It is expressly contemplated that both the broad and narrow interpretations may apply to all aspects and embodiments of the present invention. In other words, the word "comprising" and its synonyms may be replaced by the phrase "consisting of" or the phrase "consisting essentially of" or their synonyms, and vice versa.

[0099] The phrase "consisting essentially of" and its pseudonyms may be interpreted herein to mean that a material may have a small amount of impurities present. For example, the material may be greater than or equal to 90% pure, such as greater than 95% pure, such as greater than 97% pure, such as greater than 99% pure, such as greater than 99.9% pure, such as greater than 99.99% pure, such as greater than 99.999% pure, such as 100% pure.

[0100] As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a composition" includes a mixture of two or more such compositions, and the like.

[0101] The term "dalton" refers to the atomic mass unit, and the terms are used interchangeably.

[0102] Without being bound by theory, it is believed that the α-cyclodextrin crystalline domain in the super-shrinkable film disclosed herein is surrounded by semi-crystalline PEO domains, wherein the α-cyclodextrin crystalline domains are cross-linked with the PEO domains. Under uniaxial cold stretching, plastic deformation occurs in the PEO domains. Simultaneously, the PEO crystallites and chains in these domains begin to orient, and then the orientation is fixed by the newly formed PEO crystallites. When wetted, water penetrates into these domains and destroys the PEO crystallites, thereby causing the retraction of the PEO chains, to cause the desired super-shrinkage. Conveniently, a considerable portion (if not all) of the super-shrinkable properties of the film can be recovered by drying the wet film and then cold stretching.

[0103] In certain embodiments of the present invention, the oriented polyethylene oxide crystalline domains in the supershrinkable film may exhibit anisotropy in the dry state prior to contact with water.

[0104] In certain embodiments of the present invention, the super-shrinkable film can exhibit a shrinkage rate of 10 to 50% / s relative to its original length after being wetted with water. In a specific embodiment of the present invention, the super-shrinkable film can exhibit a shrinkage rate of about 12% / s relative to its original length after being wetted with water. It should be understood that the shrinkage percentage refers to the original length of the super-shrinkable film.

[0105] It should be understood that any suitable polyethylene oxide: α-cyclodextrin weight ratio can be used herein. Suitable weight: weight ratios of polyethylene oxide: α-cyclodextrin that may be mentioned herein include, but are not limited to, polyethylene oxide: α-cyclodextrin weight: weight ratios that may be 3: 1 to 1: 10, such as 1: 1.5 to 1: 9, such as 1: 1.6 to 1: 3.33, such as 2: 5 to 3: 5, such as about 2: 5, or such as about 3: 5.

[0106] The super-shrinkable films disclosed herein may be films to which one or more of the following apply:

[0107] (a) The super shrinkable film can be stable at a temperature below 60° C. and a relative humidity below 70%;

[0108] (b) polyethylene oxide may have a number average molecular weight of 500,000 to 7,000,000 Daltons, such as 750,000 to 5,000,000 Daltons, such as 1,000,000 to 3,000,000 Daltons, such as about 2,000,000 Daltons; and

[0109] (c) The super-shrinkable film may not include a crystalline inclusion complex domain formed by poly(pseudo)rotaxane or polyrotaxane formed by α-cyclodextrin and polyethylene glycol having a number average molecular weight of 500 to 10,000 Daltons.

[0110] The super-shrinkable films of the present invention can be stable at temperatures of up to 60°C at relative humidity (RH) less than or equal to 70%. Therefore, in some embodiments of the present invention that may be mentioned herein, the super-shrinkable films of the present invention can have a shrinkage strain of less than 10% when stored at room temperature (25°C) at a relative humidity less than or equal to 70% for 48 hours. Although the super-shrinkable films of the present invention may partially shrink when stored (for example, for 48 hours) at a RH greater than 70%, they can even be stable at an extremely high RH of 97% for at least 5 minutes. This means that the super-shrinkable films of the present invention can be stable for a long enough time to perform the wound closure process even at extremely high relative humidity. Therefore, in some embodiments of the present invention that may be mentioned herein, the super-shrinkable films of the present invention can have a shrinkage strain of less than 10% when stored at room temperature at a relative humidity less than or equal to 97% for 5 minutes, or at a temperature of up to 60°C at a RH of 60%.

[0111] Figure 36 The humidity stability of the super shrinkable film of the present invention is shown in the figure. The figure shows the shrinkage strain of the super shrinkable film of the present invention at 25°C under different relative humidity over time. Figure 36 As can be seen, the super-shrinkable film was stable when stored at a relative humidity of up to 69% for 48 hours. At 75% and 84% relative humidity for 48 hours, the super-shrinkable film partially shrank, while at 94% and 97% relative humidity for 48 hours, the film shrank significantly. However, even at the maximum humidity tested, the super-shrinkable film remained stable for at least 5 minutes, allowing time for the wound closure process to proceed.

[0112] In certain embodiments of the present invention that may be mentioned herein, the super-shrinkable film may have a Young's modulus of 50 MPa to 1 GPa, such as 200 to 850 MPa, such as 400 to 700 MPa, such as about 600 MPa. It should be understood that the above values ​​are related to the dry super-shrinkable film. Therefore, the super-shrinkable film may have a Young's modulus of 100 kPa to 2 MPa, such as 200 kPa to 1 MPa after being wetted with water, and after the wet super-shrinkable film is dried, the Young's modulus may be hundreds of MPa, such as 100 MPa to 700 MPa.

[0113] It will be appreciated that the supershrinkable film according to the present invention may have undergone some form of stretching to provide the oriented polyethylene oxide domains. For example, the supershrinkable film may have undergone longitudinal stretching to provide the oriented polyethylene oxide domains, wherein the longitudinal stretching results in a film length that is 200 to 1,000%, such as 250 to 700%, such as 300 to 500%, such as about 400%, of the original length of a freestanding film material comprising:

[0114] α-cyclodextrin crystalline domains; and

[0115] Unoriented polyethylene oxide domains physically cross-linked with crystalline inclusion complex domains.

[0116] In an embodiment of the present invention, the super shrinkable film may be a film that is applicable to one or more of the following:

[0117] (i) the super-shrinkable film can shrink by 35 to 65% of its original length after being wetted with water;

[0118] (ii) the maximum shrinkage stress of the super shrinkable film may be 2.5 to 7 MPa, such as 2.7 to 6.5 MPa, such as 3 to 6 MPa; and

[0119] (iii) The energy density released by the super-shrinkable film upon contact with water may be 450 to 1,800 kJ / m 3 , such as 480 to 1,730 kJ / m 3 , such as 600 to 1,300 kJ / m 3 , such as 630 to 1,240 kJ / m 3 .

[0120] For the avoidance of doubt, it is expressly contemplated that where multiple numerical ranges relating to the same feature are recited herein, it is intended that the endpoints of each range be combined in any order to provide further contemplated (and implicitly disclosed) ranges.

[0121] For example, the energy density released by a super-shrinkable film upon contact with water may be:

[0122] 450 to 480 kJ / m 3 450 to 600 kJ / m 3 450 to 630 kJ / m 3 , 450 to 1,240 kJ / m 3 , 450 to 1,300 kJ / m 3 , 450 to 1,730 kJ / m 3 450 to 1,800 kJ / m 3 ;

[0123] 480 to 600 kJ / m 3 , 480 to 630 kJ / m 3 480 to 1,240 kJ / m 3 , 480 to 1,300 kJ / m 3 , 480 to 1,730 kJ / m 3 480 to 1,800 kJ / m 3 ;

[0124] 600 to 630 kJ / m 3 , 600 to 1,240 kJ / m 3 , 600 to 1,300 kJ / m 3 , 600 to 1,730 kJ / m 3 , 600 to 1,800 kJ / m 3 ;

[0125] 630 to 1,240 kJ / m 3 , 630 to 1,300 kJ / m 3 , 630 to 1,730 kJ / m 3 , 630 to 1,800 kJ / m 3 ;

[0126] 1,240 to 1,300 kJ / m 3 1,240 to 1,730 kJ / m 3 1,240 to 1,800 kJ / m 3 ;

[0127] 1,300 to 1,730 kJ / m 3 1,300 to 1,800 kJ / m 3 ;and

[0128] 1,730 to 1,800 kJ / m 3 .

[0129] Advantages associated with the supershrinkable films disclosed herein include, but are not limited to, one or more of the following.

[0130] a. The ingredients are commercially available and non-toxic, showing excellent biocompatibility.

[0131] b. The production of α-CD / PEO films is a simple mixing and stirring process and is entirely water-based. SC membranes can be prepared by stretching CD / PEO at ambient temperature (cold stretching). This process allows for large-scale production.

[0132] c. SC membranes are free-standing, flexible, and translucent films with a thickness of tens of micrometers.

[0133] d.SC membrane has anisotropic structure and anisotropic mechanical properties.

[0134] The SC membrane is stable under ambient conditions and exhibits large (~50%) and rapid (12% / s) shrinkage in response to water, as well as ultra-large shrinkage stress (~6 MPa) and output power density (~1028 kJ / m 3 ). The shrinkage characteristics are adjustable.

[0135] The super-shrinkable film disclosed herein can be conveniently formed from a freestanding film comprising crystalline α-cyclodextrin domains and non-oriented polyethylene oxide domains physically cross-linked with crystalline inclusion complex domains. Thus, in a further aspect of the present invention, there is provided a method for forming the super-shrinkable film as described above, comprising the steps of:

[0136] (ai) Providing a freestanding film comprising:

[0137] α-cyclodextrin crystalline domains; and

[0138] Non-oriented polyethylene oxide domains physically cross-linked to crystalline inclusion complex domains, wherein:

[0139] The polyethylene oxide has a number average molecular weight of 200,000 to 10,000,000 Daltons; and

[0140] (aii) stretching a film by applying strain so that the elongation of the film reaches 100% to 300% of its original length to provide a super-shrinkable film.

[0141] The method may further include repeatedly stretching the ultra-shrinkable film by applying strain to obtain a desired length. Any suitable desired length may be used herein relative to the original length of the freestanding film. For example, the desired length may be 200 to 1,000%, such as 250 to 700%, such as 300 to 500%, such as approximately 400%, of the original length of the freestanding film.

[0142] It will be appreciated that in order to stretch the freestanding film (or the resulting "intermediate" super-shrinkable film) to its desired final length, strain must be applied. Any suitable strain may be applied in these steps. For example, the strain may be 10 to 100 MPa, such as 25 to 75 MPa, such as about 50 MPa.

[0143] Any suitable stretching speed may be applied in the stretching step. For example, stretching may involve a stretching speed of 0.1 to 5 mm / s, such as about 2 mm / s.

[0144] In embodiments of the present invention that may be mentioned herein, one or both of the following may apply:

[0145] (aa) polyethylene oxide may have a number average molecular weight of 500,000 to 7,000,000 Daltons, such as 750,000 to 5,000,000 Daltons, such as 1,000,000 to 3,000,000 Daltons, such as about 2,000,000 Daltons; and

[0146] The (ab) super-shrinkable film may not include a crystalline inclusion complex domain formed of a poly(pseudo)rotaxane or a polyrotaxane formed of α-cyclodextrin and polyethylene glycol having a number average molecular weight of 500 to 10,000 Daltons.

[0147] It will be appreciated that the freestanding membrane may be conveniently obtained by a process comprising the following steps:

[0148] (bi) providing a composition comprising α-cyclodextrin and a solvent;

[0149] (bii) adding poly(ethylene oxide) (PEO) to the composition and aging it for a period of time at a temperature of 40 to 80° C., such as about 60° C., to provide a freestanding membrane precursor solution; and

[0150] (biii) drying the freestanding membrane precursor solution to provide a freestanding membrane precursor.

[0151] Further details of the methods disclosed herein are provided in the accompanying Examples.

[0152] As described herein, the super-shrinkable film can be used as a wound dressing. Therefore, in a further aspect of the present invention there is provided a super-shrinkable wound dressing comprising:

[0153] a first layer of a supershrinkable film as described herein, having a first surface and a second surface; and

[0154] A second layer of adhesive material is applied to the first surface of the first layer, wherein the adhesive material does not cause supershrinkage of the supershrinkable film.

[0155] Any suitable adhesive material can be used in the ultra-shrinkable wound dressing of the present invention, as long as it meets the above requirements. For example, the adhesive material can be one in which a drop of the adhesive material has a contact angle of 0° to 30°, such as 5° to 25°, or even 10° to 20° on the surface of the ultra-shrinkable film.

[0156] In a particular embodiment of the present invention, the adhesive material may be a cyanoacrylate adhesive, such as a cyanoacrylate tissue adhesive. In a more particular embodiment of the present invention, the adhesive material may be selected from one or both of N-butyl-2-cyanoacrylate and 2-octyl-cyanoacrylate.

[0157] It will be appreciated that the super-contractible wound dressing may be used to treat wounds. Accordingly, further aspects of the present invention disclose:

[0158] (ZA) a method of treating a wound, the method comprising the step of applying a super-contractible wound dressing as described herein for a period of time to assist wound healing;

[0159] (ZB) Use of a super-contractible wound dressing as described herein for wound healing; and

[0160] (ZC) Use of the super-contractible wound dressing as described herein in the manufacture of a medicament for treating a wound.

[0161] Advantages associated with the supercontractile wound dressings disclosed herein include, but are not limited to, one or more of the following.

[0162] a. SC tapes are flexible, thin, and translucent. They easily adhere to the curvy, soft skin. Because they are translucent, users can clearly observe the wound beneath the film.

[0163] b. SC tape has an anisotropic structure. During implementation, users can adjust the width of the SC tape by simply tearing it according to the size of the wound.

[0164] c. Different people have different skin tensions due to differences in gender, age, and body fat percentage. Furthermore, skin in different areas also has different tensions. The SC tape disclosed herein can generate uniform tension, which is sufficient to meet the needs of skin with different skin tensions.

[0165] d. The application process is very simple and can be completed with one hand in less than 1 minute. No additional equipment is required. This SC tape is particularly suitable for emergency applications and self-care treatments.

[0166] As described in this article, super-shrinkable films can be transformed into super-shrinkable wound dressings simply by applying a suitable adhesive, enabling them to be used for skin wound closure treatment. The automatic wound closure performance and simple implementation process make them suitable for emergency and self-treatment applications. The simple manufacturing process makes them easy to mass-produce. Their excellent stability means that they can be stored and used under ambient temperature conditions. The ultra-large contractile force, work density and adjustable size make them suitable for a variety of skin and wound types of different sizes and locations. In addition, SC tape is a 2D planar film that can cover the entire wound, which can realize smart wound monitoring and drug delivery by integrating sensors and drugs into polymer materials.

[0167] By simply combining PEO with α-CD, the present invention demonstrates that the SC membrane has significant water-induced shrinkage and a high work density. Based on this, the present invention also discloses an SC tape that can squeeze healthy human skin when wet, with a displacement of >30%. The SC tape can be used for skin wound closure therapy. In vivo animal experiments have verified that the SC tape can effectively close wounds, promote wound healing, and accelerate hemostasis. By further optimizing and combining other components, the disclosed SC membrane can also help solve problems such as creating artificial muscles and developing smart flexible sensors (ACS Nano 2023, 17, 5211).

[0168] Further aspects and embodiments of the invention will now be described with reference to the following non-limiting examples.

[0169] Example

[0170] Material

[0171] α-Cyclodextrin (α-CD) and polyethylene oxide (PEO, Mw = 2,000,000) were purchased from Sigma-Aldrich. H&E staining kit (G1003), Masson trichrome staining kit (G1006), anti-CD68 rabbit pAb (GB113109) and goat anti-rabbit HRP secondary antibody (G1213) were purchased from Wuhan Service Biotechnology Co., Ltd. Viability / cytotoxicity kit (Invitrogen TM ) was purchased from ThermoFisher Scientific.

[0172] Example 1. Preparation of super shrinkable (SC) film

[0173] We prepared the SC membrane in two steps: (1) making a free-standing α-CD / PEO film ( Figure 5 ), and (2) mechanical training of α-CD / PEO films by repeated cold stretching ( Figure 6 ).

[0174] Fabrication of free-standing α-CD / PEO films

[0175] α-CD (6 g) is typically added to deionized H2O (30 ml). The mixture is then incubated in a 60°C oven for 30 min to obtain a uniform solution. Different amounts of PEO aqueous solution (4 wt%) (for example, for a mass ratio of α-CD / PEO of 5:3, the amount of PEO solution is 90 g) are then mixed with the α-CD solution and mechanically stirred for 10 min to obtain a thick mixture. For mass ratios of 5:2, 10:3, and 9:1, additional water (30 ml, 45 ml, and 73.33 ml, respectively) is added before mechanical stirring. Additional water can adjust the viscosity of the mixture to facilitate subsequent defoaming and subsequent film casting. Next, the mixture in a sealed glass bottle is incubated at 60°C overnight to remove internal bubbles. The mixture is then centrifuged at 5000 rpm for 5 min to further remove bubbles. Finally, the mixture is cast on a culture dish and dried at 60°C overnight to evaporate the H2O. After peeling from the culture dish, free-standing α-CD / PEO films were obtained. Their thickness could be adjusted by the total amount of the cast mixture.

[0176] Manufacturing SC film by cold stretching

[0177] SC membranes were prepared by repeated cold stretching processes (C42, MTS Systems Corporation tester) at room temperature. The α-CD / PEO membrane was cut into fragments of rectangular geometry. First, the α-CD / PEO film was stretched to 400% strain (5:3α-CD / PEO membrane) or 300% strain (10:3α-CD / PEO membrane) at a deformation rate of 2mm / s. Secondly, after resetting the parameters of the sample (length, width and thickness after yield), the membrane was subjected to repeated cold stretching. For each cycle, the sample was stretched to a preset stress (50MPa for 5:3α-CD / PEO and 40MPa for 10:3α-CD / PEO) and returned to the initial position by unloading at a crosshead speed of 2mm / s. Using this method, we elongated the membrane to 700% (5:3SC membrane) and 500% (10:3SC membrane). SC membranes with different elongations were prepared by this cold stretching method.

[0178] Results and Discussion

[0179] We fabricated SC membranes by uniaxial cold stretching of α-CD / PEO membranes prepared by solvent-casting an aqueous mixture of α-CD and PEO ( Figure 5 Pure PEO membranes dissolve immediately in water (Nat. Commun. 2019, 10, 2893). By adding α-CD, we enhanced the underwater stability of α-CD / PEO membranes ( Figure 8 ). Underwater stability is further discussed in Example 2.

[0180] Example 2. Water Stability and Ductility of α-CD / PEO and SC Membranes

[0181] Pure PEO films dissolve immediately in water, while α-CD / PEO films dissolve gradually over several days. Therefore, we first investigated the effect of the mass ratio of α-CD to PEO on their water stability. In addition to stability, stretchability is crucial for the preparation of shrinkable films, as shrinkable polymers require oriented polymer chains, which is typically achieved through a stretching process.

[0182] Mechanical testing

[0183] Mechanical testing was performed by using a mechanical tester (C42, MTS Systems Corporation) with a 50 N load cell.

[0184] Water stability test

[0185] Figure 8The water stability test is shown. The SC membrane (initial weight is m0) was soaked in water for different times. Subsequently, the wet SC membrane was taken out and allowed to dry. The dried membrane (m 干 ). The mass ratio is calculated according to equation (1).

[0186]

[0187] Measurement of stress-strain curves and Young's modulus

[0188] Strain-stress curves were obtained using a crosshead speed of 2 mm / s. Figure 9 and Figure 10 Stress-strain curves and Young's modulus are shown. Young's modulus was calculated by calculating the slope of the linear elastic region on the stress-strain curve (strain < 5%).

[0189] Results and Discussion

[0190] Water stability tests showed that the higher the α-CD content, the more stable the membrane was, until a mass ratio of 9:1 was reached (α-CD content, 90 wt%). Stability was greatly improved when the mass ratio was between 5:3 and 10:3. When the mass ratio was 5:3 (α-CD content, 62.5 wt%) and 10:3 (α-CD content, 76.9 wt%), the membrane retained ~92 wt% and 95 wt% of its original mass, respectively, after being immersed in water for 2 h. Figure 8 However, when the α-CD content was further increased to a mass ratio of 9:1, the stability decreased.

[0191] Stress-strain curve at room temperature ( Figure 9 ) shows that the α-CD / PEO film yields at a strain below 5% and can be stretched to several times its original length. Figure 9 ) shows that the higher the α-CD content, the larger the Young's modulus of the film, but the lower the fracture strain ( Figure 10 ). When the mass ratio increases from 1:3 to 9:1, the Young's modulus increases from ∼300 MPa to ∼850 MPa, while the fracture strain decreases from 1000% to 3% ( Figure 10 ).

[0192] Example 3. Mechanical training of α-CD / PEO membrane by repeated cold stretching

[0193] We found that mechanical training of the membrane by repeated cold stretching can produce a membrane with an elongation greater than its fracture strain. Based on its ductility and underwater stability disclosed in Example 2, α-CD / PEO membranes with a mass ratio of 5:3 and 10:3 were selected for mechanical training. By repeated cold stretching, SC membranes ( Figure 6 and Figure 7 ).

[0194] Measurement of elongation of SC films

[0195] The elongation is calculated as follows (Equation (2)):

[0196]

[0197] Where L' is the stretched length, and L0 is the original length.

[0198] Results and Discussion

[0199] During repeated cold stretching, the 5:3 and 10:3 SC films easily broke when the elongation exceeded 700% and 500%, respectively ( Figure 6 and Figure 7 ).

[0200] By repeatedly cold stretching the yielded α-CD / PEO (5:3) film at an optimal preset stress of 50 MPa, we can obtain SC films with elongations ranging from 200% to 700% ( Figure 11a For the α-CD / PEO with a mass ratio of 10:3, the optimal preset stress was 40 MPa, the elongation was between 200% and 500%, and it was easy to break when the elongation was higher than 500%. The prepared SC membrane was free-standing, flexible and stable under ambient conditions ( Figure 11b ). In addition, the SC membrane is translucent, which is beneficial because it facilitates observation of the wound under the SC membrane.

[0201] Example 4. Tear test of SC film

[0202] The width of the SC membrane can be adjusted by tearing during its application in wound closure to accommodate wounds of different sizes. This paper discloses tearing tests and related research on the SC membrane.

[0203] Tear test of SC film

[0204] A small linear notch was cut into the SC film along the cold stretching direction. The tear test was then performed on a mechanical tester, where clamps held the film to the right and left of the notch.

[0205] Figure 12 A tear test is depicted. This anisotropic structure imparts anisotropic mechanical properties to the SC membrane. When tearing in the tensile direction, the tear force is less than 0.04 N, and the membrane remains unstretched. Conversely, tearing in the transverse direction results in a tear force exceeding 1.2 N and causes membrane deformation. Therefore, by tearing in the tensile direction during wound closure applications, users can customize the width of the SC membrane to accommodate wounds of varying sizes.

[0206] Field emission scanning electron microscopy (FESEM)

[0207] FESEM images were captured at an accelerating voltage of 1 kV using a JEOL 7800. All samples were directly observed without coating with a conductive layer (Au or Pt).

[0208] Two-dimensional wide-angle X-ray diffraction (2D-WAXS)

[0209] 2D-WAXS was performed in transmission mode using a Nano-inXider system from Xenocs France. The chamber was vacuum, and the exposure time for each measurement was 5 min. The radiation source was Ka radiation (λ = 0.154 nm), operated at 50 kV and 0.6 mA, using a semiconductor detector (Pilatus, Dectris, 100 K).

[0210] Results and Discussion

[0211] The tearing test showed that the force was less than 0.04 N when tearing in the tensile direction and did not cause deformation, while the force was large when tearing in the transverse direction and caused deformation of the film ( Figure 12 This phenomenon is due to their anisotropic structure, as demonstrated by field emission scanning electron microscopy (FESEM) and two-dimensional wide-angle X-ray diffraction (2D-WAXS) results.

[0212] Field emission scanning electron microscopy (FESEM) observations showed that the SC membrane had an anisotropic structure with a rough and dense surface and no porous structure ( Figure 13 ab and 13d). Its longitudinal section shows an oriented morphology, which is similar to that of stretched pure PEO film ( Figure 13 c). 2D-WAXS results show that after cold stretching, the scattering rings belonging to PEO crystallites become anisotropic, while the scattering rings belonging to α-CD remain isotropic ( Figure 14 ac). The results show that the PEO microcrystalline domains are oriented in the SC film. The pattern of the wetted and then dried SC film returned to isotropy, indicating that water destroyed the anisotropic structure ( Figure 14 d). Therefore, in the SC membrane, α-CD forms a channel-type microcrystalline structure that crosslinks the PEO microcrystalline domains. This anisotropic structure also gives the SC membrane anisotropic mechanical properties. When we tear the SC membrane along the tensile direction, the tearing force is less than 0.04N, and the membrane does not deform. However, when we tear it along the transverse direction, the tearing force exceeds 1.2N, and the membrane deforms ( Figure 12 Therefore, by tearing along the stretching direction during wound closure application, users can customize the width of the SC membrane to accommodate wounds of different sizes ( Figure 12 ).

[0213] After mechanical training, the PEO domains are stretched and temporarily immobilized by PEO crystallites. When wetted with water, they regain isotropy because water disrupts the PEO crystallites, causing the retraction of the PEO chains and leading to supercontraction.

[0214] Example 5. Water-responsive super-shrinkable properties of SC membranes

[0215] This example studies the water-responsive super-shrinkability of SC membranes. The Young's modulus of the membranes was measured according to the protocol disclosed in Example 2. The membrane disclosed in this example is the same as the membrane in Example 4.

[0216] In wound closure applications, SC membranes should act as actuators, generating forces to bring the wound edges together. We then characterized their actuation properties, such as contractile stress and output work density.

[0217] Measurement of shrinkage strain

[0218] The SC membrane was cut into a rectangle of 40 mm × 2 mm. After soaking in water for 1 minute, the shrinkage length of the SC membrane was recorded. The shrinkage strain was calculated as follows (Equation (3)):

[0219]

[0220] Where L' is the post-contraction length, and L is the pre-contraction length.

[0221] Measurement of shrinkage stress

[0222] Shrinkage stress (shrinkage force per unit cross-sectional area) was measured by spraying water onto SC films with a fixed test length (-20 mm) on a mechanical tester. Shrinkage stress was recorded as a function of time.

[0223] Measurement of released energy density

[0224] The released energy density was measured by shrinkage stress-displacement curve (Nature, 2012, 489, 133; Sci. Adv., 2020, 6, eabd2520). For each test, the starting length of the SC film was fixed to 20 mm on the mechanical tester. Then, water was sprayed on it within 1 second to release the stored elastic energy. After about 1 second, the fixture holding the sample was retreated at a crosshead speed of 1 mm / s until the shrinkage force became zero. The stress-displacement curve was recorded. The released energy density was calculated as follows (Equation (4)):

[0225]

[0226] where U is the total released energy, which is the area under the force-displacement curve, V is the volume of the SC membrane before contraction, and S σis the area under the shrinkage stress-displacement curve, and L is the original length of the tested SC membrane.

[0227] Output power density measurement

[0228] The output power density was calculated by a lifting experiment. A load of 5 g to 50 g was suspended using an SC membrane (30 mm × 3 mm). After dripping water, the SC membrane contracted and lifted the load. The lifting displacement ΔL was recorded. The output power density was calculated using the equation (Equation (5)):

[0229]

[0230] where ΔL is the displacement of lift, m is the load weight, g is the acceleration due to gravity, and V is the volume of the SC membrane before contraction.

[0231] Results and Discussion

[0232] When wetted by immersion in water, the SC membrane shrinks rapidly (~12% / s) and significantly (~35% to ~65%) and transforms into an elastic hydrogel membrane ( Figure 15 a).

[0233] Shrinkage strain and Young's modulus after shrinkage can be adjusted by elongation ( Figure 15 bc). The adjustable shrinkage strain of the SC film is in the range of ∼35% to ∼65%, while the Young's modulus after shrinkage is in the range of ∼200 kPa to ∼2 MPa. With the increase of elongation, the shrinkage strain of the SC film increases, while the Young's modulus after shrinkage decreases ( Figure 15 bc). At comparable elongation, the 10:3SC film exhibits higher shrinkage strain and post-shrinkage Young's modulus than the 5:3SC film. This can be explained by the α-CD / PEO structure, in which soft (when wet) PEO semicrystalline domains are cross-linked by hard α-CD microcrystalline domains. Increasing the α-CD content leads to a higher cross-link density, which in turn reduces permanent plastic deformation caused by PEO chain sliding during cold stretching. Higher cross-link density and a higher proportion of the hard component lead to a higher post-shrinkage Young's modulus.

[0234] For wound closure applications, the SC membrane needs to act as an actuator, generating a contraction force to bring the wound edges closer together. We further characterized other driving properties of the SC membrane, such as contraction stress and output power density. After spraying water, the SC membrane instantly generates contraction stress ( Figure 16 ).

[0235] For the SC film (5:3), the maximum shrinkage stress increased from ∼3 MPa to ∼7 MPa, and the elongation increased from 250% to 700% ( Figure 17For the SC (10:3) film, the maximum shrinkage stress increased from 2.7 MPa to 6 MPa, and the elongation increased from 200% to 500% ( Figure 17 The SC film (5:3, 500%) used here has a thickness of about 40 μm. Therefore, the maximum shrinkage force per unit width is about 2.4 N / cm. Both films exhibit comparable maximum shrinkage stress at the same elongation.

[0236] We then compared the shrinkage stress and Young's modulus after shrinkage with those of other reported shrinkable films.These SC films were elastic films with moderate water content (~67%) after shrinkage, resulting in shrinkage stress of several MPa. This is significantly higher than the shrinkable hydrogels of several kilopascals to several hundred kilopascals (Nat. Biomed. Eng. 2022, 6, 1118; Mater. Des. 2020, 194, 108916; Sci. Adv. 2020, 6, eabd2520; J. Mater. Chem. A 2021, 9, 15937), and even exceeds conventional (~2 kPa) (Science Advances. 2019, 5(7), eaaw3963; Materials & Design. 2020, 194, 108916) and high power density shrinkable hydrogels (tens of kilopascals) (Science Advances, 2020, 6(47), eabd2520; Journal of Materials Chemistry A.2021,9(29),15937-15947), stimulus-responsive liquid crystal elastomer films, including thermoresponsive and photoresponsive liquid crystal polymers (LCPs), liquid crystal polymers (LCEs) and polyolefin elastomers (J.Am.Chem.Soc.2019,141,14364; Adv.Funct.Mater.2020,30,2002451; Macromolecules.2021,54(12),5397-5409; Macromolecules 2001,34,5868; Adv.Mater.2015,27,3883; Nat.Commun.2021,12,2916; Adv.Mater.2021,33,2106175).

[0237] Although the Young's modulus after shrinkage is lower than that of some shrinkable LCE and polymer films, water stimulation is more convenient and more suitable for the human body compared to high temperature and light stimulation that require special equipment. In addition, for wound closure on the skin, the wet SC film will dry again under ambient conditions within 30 minutes after shrinkage and recover the Young's modulus in the range of hundreds of MPa ( Figure 12 and Figure 18 ).

[0238] The effectiveness of wound closure depends not only on the maximum contractile force but also on the work that can be done during contraction. For actual wound closure, the SC membrane should contract to resist skin tension and approximate the wound edges. Therefore, we calculated the energy density released (Sci. Adv. 2020, 6, eabd2520; Nature 2012, 489, 133) ( Figure 19 ) Calculate the released energy density based on the shrinkage stress-displacement curve ( Figure 20 For the 5:3SC film, the released energy density is from 630 kJ / m 3 Increased to ~1730kJ / m 3 , the elongation increases from 200% to 700%. For the 10:3SC film, the released energy density increases from 480 kJ / m 3 Increased to ~1240kJ / m 3 , the elongation increased from 200% to 500%. At the same elongation, the released energy density of SC membrane (5:3) and SC membrane (10:3) is comparable. However, both are much higher than the reported high power density shrinkable hydrogel (Sci. Adv. 2020, 6, eabd2520), which released an energy density of about 15.3 kJ / m 3 According to structural characterization, the PEO domains cross-linked by α-CD crystalline domains are oriented and temporarily fixed, thereby storing elastic energy. A higher α-CD content means a higher permanent cross-linking density, which reduces permanent plastic deformation during cold stretching and increases recovery upon wetting. However, a higher α-CD content also means a lower PEO content, i.e., domains that store entropic energy. These two effects cancel each other out, resulting in comparable energy densities for the 5:3SC and 10:3SC films.

[0239] Then, we calculated the output power density under load (IEEE J. Ocean. Eng. 2004, 29, 706; IEEE Trans. Robot. 2019, 35, 761). Based on the above preparation process and shrinkage performance, we selected 5:3SC films with elongation of 500% and 400% and 10:3SC films with elongation of 400% as candidates for water-shrinkable tapes, and measured their output power density through lifting experiments (J. Am. Chem. Soc. 2019, 141, 14364; ACS Macro Lett. 2020, 9, 1507)( Figure 21 and Figure 22 b). SC membrane (5:3, 500%) lifted a 10 g load within seconds when wet ( Figure 21a). After redrying, the membrane further lifted the load to a higher position. Here, the output work density is calculated using the work done by the SC membrane when it is wetted within 1 minute after reaching equilibrium before redrying. The SC membrane weighing about 4 mg can lift a load of 40 g, which is 10,000 times its own weight ( Figure 22 ). The relationship between output power density and load weight is as follows Figure 23 The maximum output power density of the SC membrane (5:3, 500%) is 1028 kJ / m 3 , which is higher than that of SC membrane (5:3, 400%) of ~886kJ / m 3 and SC membrane (10:3, 400%) of ~833 kJ / m 3 .

[0240] The output power density of SC membranes exceeds that of various biological and synthetic shrinkable fibers and membranes ( Figure 24 ), such as skeletal muscle (~40 kJ / m 3 ) (IEEE J.Ocean.Eng.2004,29,706; IWHunter, S.Lafontaine, presented at Technical Digest IEEE Solid-State Sensor and Actuator Workshop, 22-25June1992,1992), hydrogel (15.3kJ / m 3 )(Sci.Adv.2020,6,eabd2520), light-triggered LCE (~40-80kJ / m 3 )(Adv.Funct.Mater.2020,30,2002451;Macromolecules 2021,54,5397;Adv.Funct.Mater.2020,30(32),2002451) and spider silk (~500kJ / m 3 )(J.Exp.Biol.2009,212,1990).

[0241] Although there are thermally triggered LCE (J.Am.Chem.Soc.2019,141,14364) or supramolecular polymers composed of polypropylene glycol and methylene bisphenylurea (PPG-MPU) (ACS Cent.Sci.2021,7,1657) that show extremely high output power density (1267.7kJ / m 3 and 2180kJ / m 3), but their high temperature stimulation is inconvenient to use and is incompatible with skin application. Some reported humidity-triggered artificial muscle fibers (Sci. Rep. 2016, 6, 23016; ACS Appl. Mater. Interfaces 2019, 11, 31162) have enhanced work density by twisting the structure. However, when the humidity is above 20%, they begin to actuate, which is unstable under ambient conditions, thus leading to premature contraction under ambient conditions before use. In contrast, our SC membranes are stable at ambient humidity. When the relative humidity (RH) is below 70%, they hardly contract ( Figure 25 Notably, the SC membrane did not shrink even at high RH (94% and 97%) for 5 minutes, which is sufficient to complete the wound closure process. This stability prevents shrinkage before wound application and offers potential for clinical translation and commercialization.

[0242] Example 6. Preparation of super-shrinkable tape for skin wound closure

[0243] The SC membrane is stable under ambient conditions and has a large output power density, which can generate sufficient power to close the wound. Here, we selected a 5:3 SC membrane with an elongation of 500% to demonstrate the preparation of SC tape, which exhibited a contraction strain of ∼55%, a contraction speed of 12% / s, a maximum contraction stress of ∼6 MPa, and a contraction rate of 1028 kJ / m 3 In addition to the SC membrane, the SC tape must also have an adhesive layer, which helps adhere the SC membrane to the skin around the wound. Here, cyanoacrylate tissue adhesive was selected to construct the adhesive layer.

[0244] Preparation of super-shrinkable tape

[0245] Prepare super-contractible tape by applying cyanoacrylate tissue adhesive to both ends of the SC membrane.

[0246] Contact angle and adhesion strength

[0247] To test the spreading ability of a cyanoacrylate tissue adhesive (liquid) on an SC membrane, contact angle measurements were performed (OCA 15 Pro). Specifically, a droplet of tissue adhesive was dispensed from a blunt-tip needle and suspended in air. The lower SC membrane, mounted on a flat glass slide on a sample stage, was slowly lifted until it contacted the suspended tissue adhesive droplet. An image of the solid-liquid-air contact was captured, and the contact angle was analyzed.

[0248] The adhesion properties of SC tape (SC film with cyanoacrylate tissue adhesive) were measured using a 180-degree peel test and a lap shear test (J. Polym. Sci., 1953, 10, 291; Science, 2017, 357, 378; Nature, 2019, 575, 169). The 180-degree peel test measures adhesion energy, and the lap shear test measures shear strength. Adhesion energy was calculated using the following equation (Equation (6)):

[0249]

[0250] Among them F 平台 is the measured platform force, and W is the width of the adhesion area.

[0251] In vitro biocompatibility

[0252] In vitro biocompatibility assessment involved culturing cells in SC membrane conditioned medium. SC membrane conditioned medium was prepared by incubating 5 mg of SC membrane (5:3,500%) sterilized by UV light before use in 5 ml of culture medium (DMEM) at 37°C for 24 hours. Normal human dermal fibroblasts were cultured at 400 nm per cm 2 1.5×10 4 The cells were seeded in a culture dish at a density of 100 cells and cultured for 2 days. Subsequently, the cell culture medium was replaced with SC membrane conditioned medium and original culture medium, followed by incubation for another 24 hours. Cells in original culture medium were used as a control. Viability / cytotoxicity kit (Invitrogen TM ) were used to stain the cells. Cell viability was assessed using a fluorescence microscope (Nikon ECLIPSE Ti2), where live cells emitted bright green fluorescence (Ex / Em: ˜495 nm / ˜515 nm), while dead cells emitted bright red fluorescence (Ex / Em: ˜528 nm / ˜617 nm).

[0253] Results and Discussion

[0254] SC membrane (5:3, 500%) was selected to demonstrate SC tape. The SC membrane composed of PEO and α-CD was biocompatible, as verified by viability / cytotoxicity assay ( Figure 26 In addition to the SC membrane, an adhesive layer is essential for SC tape. Here, we selected cyanoacrylate tissue adhesive to construct the adhesive layer ( Figure 27 ).

[0255] N-butyl-2-cyanoacrylate and 2-octyl-cyanoacrylate are commercially available and FDA-approved tissue adhesives for use on the skin (Mater. Sci. Eng., C 2020, 111, 110796; J. Plast. Reconstr. Aesthet. Surg. 2022, 75, 183; Wilderness Environ. Med. 2013, 24, 67; Prog. Polym. Sci. 2014, 39(7), 1375-1405; Rudawska, A. Adhesives: Applications and Properties; Intech Open, 2016; Vernengo, AJ Adhesives-Applications and Properties. 2016, 6, 111-133; Chem. Rev. 2021, 121(18), 11336-11384). There are several advantages to using cyanoacrylates to construct the adhesive layer.

[0256] First, cyanoacrylate cannot induce contraction of the SC membrane, thus avoiding premature contraction before it is adhered to the wound. Figure 28 As shown, the contact angle between the cyanoacrylate droplet and the SC membrane is approximately 20°, indicating that cyanoacrylate has good wettability on the SC membrane and can spread easily on it. Again, cyanoacrylates have the highest adhesive strength of all commercial tissue adhesives and can quickly form a bond with skin tissue. Their rapid polymerization can be triggered by water in the air or on the skin, resulting in a rapid bond formation with the tissue.

[0257] When combined with SC membranes, their adhesion to skin (ex vivo porcine skin) was further improved ( Figure 29 In addition, shear tests showed that due to strong adhesion, the tensile force did not induce interfacial shear but led to the elongation of the SC film ( Figure 29 c) This SC tape (redried) showed better adhesion on skin (pig skin) than a commercial soft medical tape (Tegaderm TM ) greater shear strength and greater ductility than commercially available hard medical tapes (cotton tapes) ( Figure 30 ).

[0258] SC membrane (5:3, 500%, 40 μm) can generate a contraction force of about 2.4 N / cm, which is much higher than the force required to close human skin wounds (lacerations or elliptical excisions) with a wound gap in the range of about 5-20 mm, which requires a force in the range of about 0.1 N / cm-0.7 N / cm (Med.Biol.Eng.Comput.1994,32(6),638-642;Med Biol Eng Comput.2012,50(2),193-198;Sci.Rep.2016,6(1),30117;IEEE Journal of Translational Engineering in Health and Medicine.2022,10,1-9). Therefore, it is expected that SC tape composed of SC membrane and strong adhesion interface can achieve automatic skin wound closure triggered by water.

[0259] Example 7. Skin Wound Closure Performance of Super Shrinkable Tape for Skin Wound Closure

[0260] Firstly, the wound closure performance was demonstrated on ex vivo porcine skin with an oval defect (10 mm × 3.5 mm). Figure 31 (i)). The implementation process is simple.

[0261] To close a skin wound, SC tape should overcome skin tension to bring the wound edges together. Because skin tension varies between different animals and body parts, we also directly evaluated the contractile properties of healthy human skin at different sites ( Figure 32 ).

[0262] Skin wound closure performance of supercontractile (SC) tape

[0263] A SC membrane with a size of approximately 40 μm × 7 mm (thickness × width) and 5 μl of N-butyl-2-cyanoacrylate skin tissue adhesive ( First, a SC tape consisting of a SC film (thickness: 40 μm, width: 7 mm) with N-butyl-2-cyanoacrylate applied on both sides was placed on an oval wound (10 mm×3.5 mm) ( Figure 31 During the implementation, tissue adhesive was applied to both ends of the SC film to form an SC tape with an adhesive area (marked by a blue dot). Since the SC tape is translucent, the wound underneath can be clearly observed. The SC tape was gently adhered to the healthy forearm, shoulder, and knee skin of the participant. Then, the adhesive area was gently pressed for 10 seconds ( Figure 31 (ii)). Strong adhesion is formed instantly within a few seconds. Due to the wet surface of the pig skin, the SC film shrinks slightly ( Figure 31(iii)). Afterwards, water was dropped on the SC tape above the wound to induce a significant contraction ( Figure 31 (iii-vi)). The contraction length of the contraction area was recorded after 1 min and 30 min. The SC membrane contracted instantly to close the wound within 10 seconds ( Figure 31 (iv-vi)). The whole process is very simple, takes only one minute, and is performed with one hand.

[0264] Results and Discussion

[0265] To demonstrate that the contractile force and work generated by the SC tape are large enough to resist skin tension to close human skin wounds at different locations, we also applied the SC tape to healthy human skin to characterize its skin contractile properties.

[0266] SC tape (thickness: ∼40 μm, width: ∼7 mm) adhered to the skin of the participants' forearms, shoulders, and knees contracted immediately upon wetting to compress the skin by >30% displacement within 1 min ( Figure 33 ).

[0267] Re-drying the SC tape within 30 minutes further induced skin contraction, increasing the contraction rate to over 40%. Re-drying the SC tape 30 minutes later further compressed the skin, reaching a displacement of 40% to 50%. These results demonstrate that the SC tape can generate sufficient force to compress human skin. Therefore, if a wound is present on the skin beneath the SC tape, it is expected to be effectively closed by the contraction of the SC tape. The entire process was completed within 1 minute, demonstrating this as a promising wound closure strategy, particularly for emergency and self-care / treatment applications.

[0268] Example 8. Comparison of wound healing efficacy

[0269] We used a rat skin incisional wound model to compare the in vivo wound healing efficacy of SC tape, sutures, and an untreated control. We also demonstrated the ability of SC tape to close bleeding wounds in this example by applying it to an in vivo rabbit model with a bleeding linear skin wound. The wound closure performance of SC tape was evaluated based on the protocol disclosed in Example 7.

[0270] Comparison of wound healing efficacy in a rat skin incisional wound model

[0271] Linear skin wounds (~1 cm in length) were created on rat skin. In the first group, SC tape was used to close the wound immediately after wetting with a water droplet. In the second group, sutures were applied to the wound. In the third group, the wound was not treated.

[0272] Supercontractile (SC) tape for bleeding linear skin wound closure in a rabbit model

[0273] In the bleeding wound closure experiment, 4 healthy New Zealand rabbits (female, ~2kg) were used. In preparation for surgery, the rabbits were anesthetized by intramuscular injection of Zoletil 50 and SumianxinII (1:2 mixture). Then, the hair covering the back (10cm×10cm) was shaved. A breathing mask was used to maintain anesthesia (isoflurane, 0.5%, spontaneous breathing). The shaved skin area was disinfected before surgery. Several sterile medical gauze pads were prepared and weighed to measure the amount of blood loss. Then, a full-thickness linear skin wound was created to expose the blood vessels. Then, the blood vessels were cut to create a bleeding skin wound. When the wound started to bleed, we gently placed the pad on the wound to absorb blood for 10 seconds. The blood loss before treatment was calculated by weighing the pad after blood absorption. Then, the wound was treated with closure strips or SC tape. A new weighing pad should be used to absorb the blood from the treated wound until the bleeding stops.

[0274] Histological assessment of wound tissue

[0275] Rats (6-8 weeks old, male) were anesthetized with 1.5% isoflurane and fixed on the operating table in a prone position. The hair on the back of the rats was removed to expose the skin and subsequently sterilized. Then, three wounds (1 cm) were cut side by side in the skin preparation area using a sharp scalpel. The right wound was a blank control sample and no closure operation was performed. The middle wound was closed with SC tape, and the right wound was sutured with medical sutures. The SC tape was sterilized with ultraviolet light for half an hour. To avoid infection, rats were kept in a specific pathogen-free (SPF) environment. After 3 or 7 days of feeding, the wounds were harvested (fixed in 4% paraformaldehyde for at least 12 hours), processed (embedded in paraffin and sliced ​​at 5 μm), and stained using standard histological procedures (H&E, Masson and immunohistochemistry). Hematoxylin and Erythrocyte Sequencing (H&E) staining kit (G1003), Masson's trichrome staining kit (G1006), anti-CD68 rabbit pAb (GB113109), and goat anti-rabbit HRP secondary antibody (G1213) were purchased from Wuhan Service Biotechnology Co., Ltd. Fiji Image J software was used to quantitatively evaluate tissue repair based on Masson's trichrome staining and CD68-positive areas. Statistical analysis was performed using OriginPro 2018.

[0276] Results and Discussion

[0277] Continuous monitoring of the wounds showed that wounds treated with SC tape healed better and left more aesthetically pleasing scars (Figure 34a). Histological results further demonstrated that SC tape promoted wound healing. On day 7 after injury, wounds treated with SC tape showed the smallest wound area in hematoxylin and eosin (H&E) and Masson's trichrome staining images. In contrast, scars in the untreated and sutured groups extended from the dermis to the subcutaneous muscle layer (Figure 34b).

[0278] In addition, the wounds treated with SC tape had denser collagen. This may be attributed to the large and uniform force generated by SC tape, which closed the wound more effectively. To further verify that SC tape promoted wound healing, we performed histological evaluation of wound tissues harvested on day 3 by analysis by experienced pathologists (Plastic and Aesthetic Res. 2015, 2, 239; Stem Cell Dev. 2021, 30, 1141) ( Figure 35 ). Here, the wounds treated with SC tape showed smaller wound gaps, more fibroblasts and early granulation tissue formation. Inflammatory cell infiltration was observed in both blank wounds and sutured wounds, indicating that a severe inflammatory response occurred. The sutured wounds also showed slight bleeding below the scar. On the contrary, the wounds treated with SC tape showed hair follicle regeneration, fibroblasts replacing necrotic muscle fibers and less inflammation. Masson trichrome staining images showed that an increase in collagen deposition could be observed in all groups, but the collagen levels in the wounds treated with SC tape were much higher than those in the suture-treated and untreated wounds (Figure 34c and Figure 34e). CD68 was immunohistochemically stained to assess the recruitment of macrophages (Figure 34d). The wounds treated with SC tape showed less immune response (Figure 34f), proving that wound recovery can be accelerated.

[0279] Commercial skin tissue adhesives cannot be applied to bleeding wounds. In our work, SC tape can close wounds in the presence of blood without the need for additional stimulation. The implementation process of super-contractile (SC) tape on bleeding linear skin wounds in a rabbit model is simple and quick, requires no special preparation, and can even be performed with one hand (Figure 34g). Once the tape is adhered to the bleeding wound, the blood underneath it triggers the SC tape to contract within 10 seconds, resulting in sufficient wound closure. We compared its wound closure performance with commercial medical closure strips (Figure 34h). Our SC tape shows better wound closure due to automatic contraction. This contraction applies mechanical compression to the wound, which helps to stop bleeding (Figure 34i).

Claims

1. A super-shrinkable film comprising: α-cyclodextrin crystalline domain; and Oriented polyethylene oxide crystalline domains physically cross-linked by said α-cyclodextrin crystalline domains, wherein: The polyethylene oxide has a number average molecular weight of 200,000 to 10,000,000 Daltons; and The supershrinkable film shrinks more than 50% of its original length upon wetting with water.

2. The super-shrinkable film according to claim 1, wherein The oriented polyethylene oxide crystalline domains exhibit anisotropy in a dry state before contact with water.

3. The super-shrinkable film according to claim 1 or claim 2, wherein: The supershrinkable film exhibits a shrinkage rate of 10 to 50% / s relative to its original length after being wetted with water.

4. The super-shrinkable film according to claim 3, wherein: The supershrinkable film exhibits a shrinkage rate of about 12% / s relative to its original length after being wetted with water.

5. A super-shrinkable film according to any one of the preceding claims, wherein The weight:weight ratio of polyethylene oxide:α-cyclodextrin is 3:1 to 1:10, such as 1:1.5 to 1:9, such as 1:1.6 to 1:3.33, such as 2:5 to 3:5, such as about 2:5, or such as about 3:

5.

6. A super-shrinkable film according to any one of the preceding claims, wherein One or more of the following applies: (a) the super shrinkable film is stable at a temperature below 60° C. and a relative humidity below 70%; (b) the polyethylene oxide has a number average molecular weight of 500,000 to 7,000,000 Daltons, such as 750,000 to 5,000,000 Daltons, such as 1,000,000 to 3,000,000 Daltons, such as about 2,000,000 Daltons; and (c) The ultra-shrinkable film does not include a crystalline inclusion complex domain formed by poly(pseudo)rotaxane or polyrotaxane formed by α-cyclodextrin and polyethylene glycol having a number average molecular weight of 500 to 10,000 Daltons.

7. A super-shrinkable film according to any one of the preceding claims, wherein The super shrinkable film has a Young's modulus of 50 MPa to 1 GPa, such as 200 to 850 MPa, such as 400 to 700 MPa, such as about 600 MPa, optionally wherein the super shrinkable film has a Young's modulus of 100 kPa to 2 MPa, such as 200 kPa to 1 MPa after being wetted with water, and after the wet super shrinkable film is dried, the Young's modulus is several hundred MPa, such as 100 MPa to 700 MPa.

8. A super-shrinkable film according to any one of the preceding claims, wherein The supershrinkable film is longitudinally stretched to provide oriented polyethylene oxide domains, wherein the longitudinal stretching results in a film having a length of 200 to 1,000%, such as 250 to 700%, such as 300 to 500%, such as about 400%, of the original length of a free-standing film material comprising: α-cyclodextrin crystalline domains; and Unoriented polyethylene oxide domains physically cross-linked with crystalline inclusion complex domains.

9. A super-shrinkable film according to any one of the preceding claims, wherein One or more of the following applies: (i) the super-shrinkable film shrinks by 35 to 65% of its original length upon wetting with water; (ii) the maximum shrinkage stress of the super shrinkable film is 2.5 to 7 MPa, such as 2.7 to 6.5 MPa, such as 3 to 6 MPa; as well as (iii) the super-shrinkable film releases an energy density of 450 to 1,800 kJ / m upon contact with water 3 , such as 480 to 1,730 kJ / m 3 , such as 600 to 1,300 kJ / m 3 , such as 630 to 1,240 kJ / m 3 .

10. A super-contractible wound dressing comprising: a first layer of the supershrinkable film according to any one of claims 1 to 9 having a first surface and a second surface; as well as A second layer of adhesive material applied to the first surface of the first layer, wherein the adhesive material does not cause supershrinkage of the supershrinkable film.

11. The super-contractible wound dressing according to claim 10, wherein: The droplet of the adhesive material has a contact angle on the surface of the super-shrinkable film of 0° to 30°, such as 5° to 25°, such as 10° to 20°.

12. The super-contractible wound dressing according to claim 10 or claim 11, wherein: The adhesive material is a cyanoacrylate adhesive, such as cyanoacrylate tissue adhesive.

13. The super-contractible wound dressing according to claim 12, wherein The adhesive material is selected from one or both of N-butyl-2-cyanoacrylate and 2-octyl-cyanoacrylate.

14. A method for forming the super-shrinkable film according to any one of claims 1 to 9, the method comprising the steps of: (ai) Providing a freestanding film comprising: α-cyclodextrin crystalline domains; and Non-oriented polyethylene oxide domains physically cross-linked to crystalline inclusion complex domains, wherein: The polyethylene oxide has a number average molecular weight of 200,000 to 10,000,000 Daltons; and (aii) stretching a film by applying strain so that the elongation of the film reaches 100% to 300% of its original length to provide a super-shrinkable film.

15. The method according to claim 14, wherein The method further comprises further repeatedly stretching the supershrinkable film by applying strain to obtain a desired length, optionally wherein the desired length is 200 to 1,000%, such as 250 to 700%, such as 300 to 500%, such as about 400% of the original length of the freestanding film.

16. The method according to claim 14 or claim 15, wherein: The strain is 10 to 100 MPa, such as 25 to 75 MPa, such as about 50 MPa.

17. The method according to any one of claims 14 to 16, wherein The stretching involves a stretching speed of 0.1 to 5 mm / s, such as about 2 mm / s.

18. The method according to any one of claims 14 to 17, wherein The polyethylene oxide has a number average molecular weight of 500,000 to 7,000,000 Daltons, such as 750,000 to 5,000,000 Daltons, such as 1,000,000 to 3,000,000 Daltons, such as about 2,000,000 Daltons.

19. The method according to any one of claims 14 to 18, wherein The ultra-shrinkable film does not include a crystalline inclusion complex domain formed by poly(pseudo)rotaxane or polyrotaxane formed by α-cyclodextrin and polyethylene glycol having a number average molecular weight of 500 to 10,000 Daltons.

20. A method of forming the freestanding membrane of claim 14, the method comprising: (bi) providing a composition comprising α-cyclodextrin and a solvent; (bii) adding poly(ethylene oxide) (PEO) to the composition and aging for a period of time at a temperature of 40 to 80° C., such as about 60° C., to provide a freestanding membrane precursor solution; as well as (biii) drying the freestanding membrane precursor solution to provide a freestanding membrane precursor.

21. A method of treating a wound, the method comprising the step of applying a super-contractible wound dressing according to any one of claims 10 to 13 for a period of time to assist wound healing.

22. Use of the super-contractible wound dressing according to any one of claims 10 to 13 for wound healing.

23. Use of the super-contractible wound dressing according to any one of claims 10 to 13 in the manufacture of a medicament for treating wounds.

Citation Information

Patent Citations

  • Improvements in or relating to Means or Apparatus for Facilitating the Laying of Machine Guns for Indirect Firing.

    GB113109A

  • Bioinspired water shrink film for shape-adaptive bioelectronics

    WO2023075689A2

Cited By

  • Self-adaptive super-contraction tendon adhesive with janus structure and preparation method of self-adaptive super-contraction tendon adhesive

    CN121534215A